PELAKSANAAN MANAJEMEN BIMBINGAN DAN KONSELING DI SMA NEGERI 1 TENJOLAYA - Rahmawati, Ima; Rinawati; Ihsan, Muzhir; Supriatna, Nana; Hana (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2023)
Students as the main focus of education delivery must receive good and appropriate service from educational service providers (School Institutions), so that the output produced is of high quality and can meet expectations to be able to adapt and be able to compete in this era. This study aims to describe the implementation of guidance and counseling service management at SMA Negeri 1 Tenjolaya. This research method uses a descriptive method with a qualitative approach with data collection techniques through interviews, observation, and documentation. The subject of this study was one of the counseling teachers at SMA Negeri 1 Tenjolaya. The results of the study show that the management of guidance and counseling services at SMA Negeri 1 Tenjolaya has been going well, as can be seen from the management functions implemented in the guidance and counseling services.